Ecological design of outdoor gardens in oil companies in Basra Governorate, Southern Refineries Company (Cuestiones de Fisioterapia, 2025)
This study aims to develop an integrated framework for the design of open outdoor spaces inoil companies' sites in Basra Governorate, in order to improve the efficiency of these sites. Theseobjectives come in response to the urgent need to design aesthetic and functional work spaces that takeinto account the environmental characteristics of the region, which contributes to enhancing the healthand safety of workers and reducing the harmful environmental impacts resulting from oil operations. Thestudy is based on an applied field methodology consisting of three main stages; the first stage begins withconducting a comprehensive field survey of the site, in the second stage, collecting information anddocumenting the current situation using photography, observations and spatial analysis techniques, andfinally, in the third stage, proposed design models are prepared using the AutoCAD program. The resultsof this study show the importance of designing outdoor spaces in oil companies' sites and their directimpact on employee comfort and productivity.